School systems in Trinidad and Tobago: A cause of deviant behaviours/violent crimes and the XYZ model of school violence - Bahall, Mandreker (Science Publishing Group, 2024)
The aetiology of violence is manifold (genetic, personal, environmental, and situational) and of major concern to Trinidad and Tobago. The school system itself (the main conduit for overall child development) might be a major contributor to poor performance, deviance, and violent behaviour. Primary and secondary school education is a strategic instrument for promoting or hindering children’s growth and development. This study aims to show the possible relationship between the school system and school performance and the potential for deviant and violent behaviour. Data were collected on the school system, school performance, and national crime levels. A literature search was also conducted on school systems, performance, and violence. Results indicate that primary school training focused on academic performance and did not cater to universal accessibility or ‘legitimate structural accessibility’ for all children, and focused on obtaining places in prestigious institutions for higher education. Since 2018, approximately 40% of the students have failed the secondary entrance assessment exam, with approximately 11% scoring less than 30%. With universal secondary school enrolment, students may be deprived further of accessibility. This may become compounded by the mixing of students of varying tendencies, behaviours, and otherwise. This continued reliance on academics satisfied the students at prestigious schools. The secondary school system brings added challenges such as the mixing of students (academics, non-academics, students with violent or deviant tendencies, etc.) of varied backgrounds and continued lack of ‘legitimate structural accessibility’. A large section of the non-academically inclined (half passing fewer than five subjects) may find themselves doing inappropriate things, eventually leading to deviance or even violent behaviour. This is further complicated by contributions from the public health system. In the public school system, students, especially those who are not academically inclined, endure further stress, anger, frustration, and eventually ending in deviant/violent behaviour. A school system with an academic focus effectively decreases ‘legitimate structural accessibility’ and opportunities. This subsequently leads to ‘non-performing students’ affecting their psyche and confidence and disturbing other students, eventually leading to deviance and criminal activity. Such a dysfunctional school system must be corrected to allow student education to be holistic. Additionally, a need exists to develop a system to screen and identify students who are at risk or display deviance, and implement corrective measures.
Keywords: Deviance; Criminal Behaviour; Holistic Education; Risks; Positive Factors; XYZ Model of School Violence; Crime Aetiology